Scalable synthesis of silicon nanoplate-decorated graphite for advanced lithium-ion battery anodes. Issue 5 (27th January 2021) - Li, Haimei; Li, Xianglong; Wang, Denghui; Zhang, Siyuan; Xu, Wenqiang; Zhu, Li-Na; Zhi, Linjie
Abstract : A silicon nanoplate-decorated graphite design is developed for lithium battery anodes via a simple ball milling process. Abstract : A silicon nanoplate-decorated graphite design is developed for lithium battery anodes via a simple ball milling process. The resultant silicon–graphite electrodes show high cycling stability with high capacity, superior rate capability, and excellent electrode stability when compared to their counterparts, attributable to two-dimensional silicon and its area-to-area contact with graphite.